INDIVIDUAL ENTREPRENEURSHIP IN RUSSIA: MEASURING DATA OF 2018 - Pinkovetskaia, Iuliia; Schennikova, Natalya; Kryukova, Liudmila (Revista Inclusiones, 2020)
The aim of this research is discussion of level development of individual entrepreneurs in Russia and its regions. Analysis data on types of economic activity and regions presented in official statistical report of 2018. Methodology of this study was based on economic-mathematical modeling. These models were functions of normal distribution. As indicators offered: number of employees and income per one individual entrepreneur, income per one employee in individual entrepreneurship, number of entrepreneurs per thousand residents in the region and number of employees in individual entrepreneurship per thousand residents. We showed that entrepreneurs in the field of wholesale and retail trade predominate in Russia.